Assessment of Groundwater Suitability for Irrigation and Livestock Purposes in Sayed Al-Shuhadaa Agricultural City, Karbala, Central Iraq - Mahmoud, Rafal Ghassan; Al Shamma’a, Ayser; Al-Ghanimy, Maithem (Iraqi Journal of Science, 2023)
The study investigates the anion and cation concentrations and their distribution in the Dammam aquifer to assess the groundwater suitability for irrigation and livestock in Sayed Al-Shuhadaa, Karbala, central Iraq. It lies between longitudes 43º 29’ 00’’ – 43º 40’ 00’’ E and latitudes (32º 17’ 00’’ – 32º22’ 00’’) N. The physicochemical properties, cations and anions were measured in 14 active wells distributed in the study area. The assessment was conducted based on the sodium adsorption rate (SAR), sodium percentage (Na%), electrical conductivity (EC), total dissolved solids (TDS), and Hydrogen number (pH). Groundwater in the study area is very good for livestock and characterised by no damage, as the rate of sodium adsorption was good. The percentage of sodium and pH values are within the permissible values for irrigation, except for some wells that have high TDS and EC, which leads to an increase in salinity.